Campus Police-Citizen Encounters: Influences on Sanctioning Outcomes - Allen, Andrea N. (American journal of criminal justice, 2015)
The vast majority of prior work on officers’ sanctioning decisions involves municipal police. An open question is whether findings from that research are generalizable to campus police, as they operate in a somewhat different context. This study explores the effect of legal and extralegal factors on campus officers’ sanctioning decisions in encounters. Data were collected through observations of campus police at a large university in the Southeastern United States. Logistic regression is used to analyze 95 campus police-citizen encounters. Findings indicate that officers more severely sanction suspects when there are more bystanders present and suspects display a negative demeanor or are visibly intoxicated. The results suggest that some but not all of the same influences affect municipal and campus police sanctioning decisions. Paths for future research are discussed.